Professores de bebês: elementos para compreensão da docência masculina na educação infantil - Aguiar Júnior, Josoé Durval (2017)
This thesis presents research that aims to analyze what happens in early childhood education schools, in nursery schools, when there is the presence of male teachers. We intend to gather elements to understand the male teaching profession in early childhood education, specifically in daycare centers, listening to the teachers in Early Childhood Education Centers in the city of São Paulo, about how they perceive their job in the process of babies’ formation. We also intend to outline those professionals’ profile and, based on official documents and legislation, describe the conditions of those male professionals’ admission in this professional space, identifying what the Municipal Department of Education has been doing to welcome and integrate those professionals in the school units. Therefore, we try to gather elements to outline those new professional teachers’ profile in early childhood education: the teachers of babies and, specifically, the male teacher of babies. This research has a qualitative nature, accomplished by means of documental analysis and electronic forms answered by 24 professionals (from 170 teachers of Early Childhood Education Centers that work in the Municipal Department of Education of São Paulo). As theoretical support, we have used texts related to the teaching profession and its specificities, with Roldão’s contribution; to the work of and in the daycare center and the performance of the teachers of babies, with Rosemberg’s, Barbosa’s and Falk’s studies; and to the issues about gender and the teaching profession in early childhood education, with Apple’s contributions. The results obtained (organized in charts and tables) allowed us to confirm the research hypothesis that: a) The early childhood education teachers that work in Early Childhood Education Centers suffer from prejudice of the school community personally (sexual orientation, temper and social conduct) and professionally (technical competence, formation, experience with the age group and reasons why they have chosen the career); and b) The educational system is still not prepared to receive such professional and support the ones involved, once there are not specific actions to welcome and guide those professionals, in their performance in daycare centers. Male teachers have been admitted in the Municipal Department of Education of São Paulo, without the discussion by the managers, teachers and parents of the resulting conflicts and problems. There are not references or political actions that have approached this theme. The municipal publications have ignored this fact so far